Interpreting the Quran’s Teachings on Religious Moderation - Ibad, Al (Research Horizon, 2023)
Religious moderation involves a balanced and non-extremist approach to religious worship. This article seeks to determine whether the Quran and Hadith, as the holy texts of Islam, contain any elements that could potentially incite violence and terrorism, particularly against individuals of other faiths. In this research, the author employs the maudhu’i tafsir method, which involves selecting a specific topic and then examining various Quranic verses and Hadiths related to religious moderation in the context of the study’s focus. The findings of this study demonstrate that the Quran and Hadith do not encourage Muslims to engage in acts of violence or religious extremism. Instead, these sources emphasize the importance of practicing religion with balance and moderation, promoting a friendly, gentle, and compassionate approach. Balance is not only encouraged in matters of faith but also regarded as essential in maintaining the harmony of life and preventing the destruction of the world.